Effect of Halal Awareness, Halal Certification, Food Ingredients Composition, Halal Marketing and Religiosity on Purchase Intention of Imported Food Products - Nida Karimah; Darwanto Darwanto (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2021)
Muslims are required to always consume halal food in accordance with Islamic orders. Halal awareness, halal certification, food ingredients composition, halal marketing and religiosity can influence consumer behavior, especially on product purchase intention. Not all food products have been labeled halal, especially the imported products. This study aims to look at the effect of halal awareness, halal certification, food ingredients composition, halal marketing and religiosity on the purchase intention of imported food products in Muslim consumers in the city of Semarang by using the Structural Equation Model (SEM). The results of the analysis show that halal awareness, halal certification, food ingredients composition, halal marketing and religiosity have a positive and significant effect on imported food products purchase intention.